ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI LINGKARAN - Sifa Ulhaq; Devi Nurul Yuspriyati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This qualitative descriptive research is where it has the goal to analyze the workmanship of junior high school students' mistakes solving on circle material. The students who attended were 22 concerned about this researcher who became the subject of students of class VIII-SMP Negeri 6 Lembang one of the Lembang District State Junior High School data used in the form of test 5 questions, after the study was described. every question of why students experience errors in the speaker on each problem number in the Circle material. Student error analysis can be done by collecting data, presenterizing data and drawing conclusionsevery question of why students experience errors in the speaker on each problem number in the Circle material. Student error analysis can be done by collecting data, presenterizing data and drawing conclusions.The result of errors in the highest hardening of problem number 5 is 72% while the lowest error result in questions numbers 1 and 4 is 45%. By. The results of the study showed that students' errors in solving problems there are errors, misunderstandings to concepts, misrepresentation in reading contained in the problem, and errors in the optimization of problems Researchers have concluded that it turns out that there are still many students who make mistakes when talking about circle material.